2019
DOI: 10.3846/transport.2019.11079
|View full text |Cite
|
Sign up to set email alerts
|

Reserve Fleet Indexed to Exogenous Cost Variables

Abstract: Identifying the optimal time to replace a passenger bus in a buses fleet has implications on the size of the reserve fleet. Such calculations rest on endogenous and exogenous economic variables: the former include operating and maintenance costs and bus depreciation; the latter include market imponderables such as the inflation and real discount rates, as well as energy costs, particularly fuel. The authors have created models for the withdrawal/replacement of buses using endogenous economic variables. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…12: Radar Map [27] There are several non-exclusive causes that make replacement equipment economical, being deterioration one of them that is manifested by excessive operating and rising maintenance costs. This subject has been researched by several authors, with interesting results, as is shown, in the field of urban passenger transport, by the references [28], [29] and [30]. There are situations in which, with the change of a current operation, an equipment loses the ability to operate efficiently, that is, the equipment becomes inadequate.…”
mentioning
confidence: 98%
“…12: Radar Map [27] There are several non-exclusive causes that make replacement equipment economical, being deterioration one of them that is manifested by excessive operating and rising maintenance costs. This subject has been researched by several authors, with interesting results, as is shown, in the field of urban passenger transport, by the references [28], [29] and [30]. There are situations in which, with the change of a current operation, an equipment loses the ability to operate efficiently, that is, the equipment becomes inadequate.…”
mentioning
confidence: 98%